Out on a limb ebook A novel. - Bonam-Young, Hannah (2023)
A hot one-night stand—and an unexpected pregnancy—lead a young woman to someone she can depend on, from the viral TikTok author of Next of Kin and Next to You . “A beautiful love story, full of joy from beginning to end!”— New York Times bestselling author Sarah Adams AN ELLE BEST BOOK OF THE YEAR Winnifred “Win” McNulty has always been wildly independent and not one to be coddled for her limb difference. Win has spent most of her life trying to prove that she can do it all on her own. With some minor adjustments, she’s done just fine. Hooking up at a costume party with the incredibly charming Bo changes everything. Win finds herself pregnant—and decides to keep the baby. While Bo is surprisingly elated to step up to the plate, Win is unsure of whether she can handle this new challenge. Together, Win and Bo decide to get to know one another as friends and nothing more while they embark on this parenting journey together. But, as they both should know by now, life rarely goes according to plan.